The role of legal status and uncertainty in the reproductive aspirations of 1.5 and second generation Mexican-origin immigrant young women: An exploratory study - Kate Coleman-Minahan; Melissa Villarreal; Goleen Samari (Elsevier, 2023)
Background: The 1.5 generation, brought to the U.S. prior to age 16, faces barriers that the second generation, U.S.-born to immigrant parents, does not, including only temporary legal protection through the Deferred Action for Childhood Arrivals (DACA) Program. Little is known about how legal status and uncertainty shape cisgender immigrant young women's reproductive aspirations. Methods: Drawing on the Theory of Conjunctural Action with attention to the immigrant optimism and bargain hypotheses, we conducted an exploratory qualitative study using semi-structured interviews with seven 1.5 generation DACA recipients and eleven second generation Mexican-origin women, 21-33 years old in 2018. Interviews focused on reproductive and life aspirations, migration experiences, and childhood and current economic disadvantage. We conducted a thematic analysis using a deductive and inductive approach. Results: Data resulted in a conceptual model on the pathways through which uncertainty and legal status shape reproductive aspirations. Participants aspired to complete higher education and have a fulfilling career, financial stability, a stable partnership, and parents' support prior to considering childbearing. For the 1.5 generation, uncertainty of their legal status makes the thought of parenting feel scary, while for the second generation, the legal status of their parents makes parenting feel scary. Achieving desired stability before childbearing is more challenging and uncertain for the 1.5 generation. Conclusions: Temporary legal status constrains young women's reproductive aspirations by limiting their ability to achieve desired forms of stability prior to parenting and making the thought of parenting frightening. More research is needed to further develop this novel conceptual model.